Childhood obesity and motor skills disorders: Scoping review (Research, Society and Development, 2022)
The objective of this study was to map and synthesize the findings on the influence of high weight/obesity on motor skills disorders in children aged zero to six years, through a scope review of productions with relevant scientific evidence regarding possible motor disorders in infants and children with high weight or obesity, considering the period between 2012 and 2022, with free access. The searches were carried out in the MEDLINE, PubMed, LILACS, Virtual Health Library – VHL databases, Web of Science, Scopus, Cochrane Library and, in the gray literature (Google Scholar), using as strategies the keywords indexed in DeCS and MeSH “infant”, “child”, “obesity”, “overweight”, “preschool”, “motor skills disorders”. Studies with observational, interventional design and systematic review were included. Of the 636 articles initially identified, 15 were eligible: 12 reported that developmental disorders are related to high weight and/or obesity, 2 did not present consistent evidence for the relationship between weight and developmental disorder, 1 presented the hypothesis that overweight/ Obesity may be a secondary consequence of developmental disorders, and 1 concluded that overweight children from low-income families are more likely to be at risk of delayed motor development. There is a scarcity of studies published in the period, justifying the need for more studies, especially randomized clinical trials.